Venous thromboembolism in patients with COVID-19: Systematic review and meta-analysis - Porfidia, Angelo (Thromb Res, 2020)
BACKGROUND: Venous thromboembolism (VTE) may complicate the course of Coronavirus Disease 2019 (COVID-19). OBJECTIVES: To evaluate the incidence of VTE in patients with COVID-19. METHODS: MEDLINE, EMBASE, and PubMed were searched up to 24th June 2020 for studies that evaluated the incidence of VTE, including pulmonary embolism (PE) and/or deep vein thrombosis (DVT), in patients with COVID-19. Pooled proportions with corresponding 95% confidence intervals (CI) and prediction intervals (PI) were calculated by random-effect meta-analysis. RESULTS: 3487 patients from 30 studies were included. Based on very low-quality evidence due to heterogeneity and risk of bias, the incidence of VTE was 26% (95% PI, 6%–66%). PE with or without DVT occurred in 12% of patients (95% PI, 2%–46%) and DVT alone in 14% (95% PI, 1%–75%). Studies using standard algorithms for clinically suspected VTE reported PE in 13% of patients (95% PI, 2%–57%) and DVT in 6% (95% PI, 0%–60%), compared to 11% (95% PI, 2%–46%) and 24% (95% PI, 2%–85%) in studies using other diagnostic strategies or patient sampling. In patients admitted to intensive care units, VTE occurred in 24% (95% PI, 5%–66%), PE in 19% (95% PI, 6%–47%), and DVT alone in 7% (95% PI, 0%–69%). Corresponding values in general wards were respectively 9% (95% PI, 0%–94%), 4% (95% PI, 0%–100%), and 7% (95% CI, 1%–49%). CONCLUSIONS: VTE represents a frequent complication in hospitalized COVID-19 patients and often occurs as PE. The threshold for clinical suspicion should be low to trigger prompt diagnostic testing.